[RE]IMAJI GLODOK MELALUI ECHOLOGY - Vito Wijaya; Maria Veronica Gandha (Jurusan Arsitektur dan Perencanaan, 2021)
An Architecture can be a memory store from a time. Many buildings or areas that have historical value are now abandoned, disintegrated, eroded by modern developments. In line with the development of the city, there are many dark histories and political issues that afflict Chinese culture and society in Indonesia. With the revocation of Presidential Instruction No. 14/1967 concerning Chinese Religion, Belief, and Customs during the Reformation period, it was replaced by the issuance of Presidential Decree (Keppres) No. 6/2000 on January 17, 2000, bringing Chinese culture back to life, then how can an Architecture and a Chinatown be able to adapt to the conditions of today and for the future without losing its identity and historical value. This project is a new embodiment for an area that includes various elements such as history, culture, economy, utilities, and education. All these aspects are formed collectively and in a community with a narrative method and connect existing elements into the concept of Echology. [RE]Image Glodok produces a project that reimagines the Chinatown area of Glodok where historical, cultural, and economic aspects can be reflected and build a new Glodok image by considering various elements that exist in the area and designing it for the sake of sustainability in the present and the future through Echology. Keywords: Chinatown; Glodok; Image AbstrakSebuah Arsitektur dapat menjadi penyimpan memori dari suatu masa. Banyaknya bangunan atau kawasan yang memiliki nilai historis kini terbengkalai, terdisintegrasi, tergerus perkembangan moderen. Sejalan dengan perkembangan kota, banyak nya sejarah kelam dan isu-isu politik yang menimpa budaya serta masyarakat Tionghua di Indonesia. Dengan dicabutnya Inpres Nomor 14 Tahun 1967 tentang Agama, Kepercayaan, dan Adat Istiadat Cina pada masa Reformasi digantikan dengan terbitnya Keputusan Presiden (Keppres) Nomor 6 Tahun 2000 pada 17 Januari 2000 membuat budaya Tionghua kembali hidup, kemudian bagaimana sebuah Arsitektur dan sebuah kawasan Pecinan mampu menyesuaikan dengan kondisi pada zaman ini dan untuk masa depan tanpa kehilangan jati diri serta nilai sejarahnya. Proyek ini merupakan perwujudan baru bagi sebuah kawasan yang mencakup berbagai unsur seperti sejarah, budaya, ekonomi, utilitas, serta edukasi. Semua aspek tersebut dibentuk secara kolektif dan berkomunitas dengan metode naratif serta mengkoneksikan elemen-elemen yang sudah ada menjadi konsep Echology. [RE]Imaji Glodok menghasilkan sebuah proyek yang mereimajikan kawasan pecinan Glodok dimana aspek sejarah, budaya dan ekonomi dapat tercerminkan dan membangun imaji Glodok yang baru dengan mempertimbangkan berbagai elemen yang ada pada kawasan serta merancangnya demi keberlangsungan di masa kini maupun masa depan melalui Echology.